Gambaran Kadar Glukosa Darah Puasa, Kadar Kolesterol Total dan Trigliserida Darah Mahasiswa Fakultas Kedokteran UKRIDA Tahun Akademik 2004/2005 - Herwati Sudiono; Sanarko Lukman Halim (Jurnal Kedokteran Meditek, 2004)
Lipid profile examination is often done to evaluate the risk of coronary heart disease, cerebrovascular disease and peripheral vascular disease. Several disorders are accompanied by lipid profile changes, e.g. diabetes mellitus, hypothyroldism, renal disease, alcoholism and AIDS. Elevated fasting blood glucose, total cholesterol aand triglyceride levels are mayor risk factors for atherosclerosis. This study evaluated 46 male and 90 female students of the medical faculty of Krida Wacana Christian university (ukrida), aged 18 to 31 years. We found one male student with a high fasting blood glucose level (140 mg/dl). None of the female students had a high fasting blood glucose level. Mean total cholesterol level was higher (198.9 mg/dl) inmale students in comparison with female students (182.8 mg/dl). Percentage of female students with a desirable cholesterol value was higher than in male students. (72.2% vs 54.4%). Percentage of female students with a borderline high and high cholesterol values were lowr than in male students. Mean triglyceride value was higher (102.2 mg/dl) in male students in comparison with female students (78.9 mg/dl). Percentage of female students with a normal triglyceride value was higher than in male students . (96.7% vs 84.8%). Percentage of female studens with a borderline high and high triglyceride values were lower than in male students. Our data suggest that preventive programs for students are recommended to decrease the prevalenceof cardiovascular risk factors. As life style changes are important for a healthier Indonesian population in the next 10-20 years, the medical faculty of Krida Wacana Christian University (UKRIDA) should play a bigger role in preventive health care programs.